A novel technique to simulate low tension gas (LTG) process in fractured reservoirs with commercially available simulator. (1st May 2020) - Ren, Guangwei
Abstract: Low tension gas (LTG) process attempts to employ microemulsion (MI) and foam to enhance oil recovery (EOR). It is challenging to model surfactant phase behavior as a function of salinity for commercially available simulators since they lack the capability to explicitly represent MI properties. In this paper, a novel approach is developed to simultaneously model foam flow and surfactant/oil/brine key characteristics, using the general framework of CMG/STARS. Measured phase behavior data is transferred into k-value based relationships with multi-components oleic phase, based on which phase viscosities are calculated with non-linear mixing equation as function of different key components. Winsor Type phase variations are tracked by a pseudo-component generated by kinetic reactions, as another invention here. The mobility control by foam is fulfilled by the novel bubble dispersion model when increasing aqueous phase viscosity through bubble characteristics. Investigations of phase viscosities, IFT and compositions in 1D and 2D section models show that the developed methodology correctly accounts for surfactant solution desaturation in matrix and for mobility control by foam flow in the fractures. As such, the developed techniques provide a methodology to model LTG process in naturally fractured reservoirs within the framework of commercially available simulators along with their limited functionalities.